A doutrina da união hipostática à luz da categoria do “encontro” e suas implicações para a promoção da paz - Madureira, José Gabriel Perissé (2023)
The objective of this thesis is to conceive and develop a “christology of the encounter” in line with the theme of peace, taking the doctrine of the hypostatic union as starting point, in the light of the theological category of “encounter” based on the philosophy of Alfonso López Quintás. In order to achieve this purpose, the concepts of “person” and “nature” (fundamental concepts in the discussions and definitions of the Chalcedonian council) are taken up again, in dialogue with the dominant concerns of our time. The analysis of some gospel accounts with an emphasis on Jesus as the “Master of the Encounter” and “God with us” brings up concrete requirements and characteristics of living together in search of the ideal of unity and of the true peace. The Kingdom of God is the Kingdom of Encounter and Peace, which all human beings are invited to enter and participate. The peace in question is not provisional and contingent (however desirable), but of that peace that the world cannot give (cf. John 14,27), and which will be called here “hypostatic peace”.